The Musical Expat: Privileged Migration and Baby Music Class in Lisbon - Snyder, Andrew (MUSICultures)

(untitled) (Canadian Society for Traditional Music / La Société canadienne pour les traditions musicales, 2023)
This article focuses on the role of children’s music education in the settlement of Lisbon, Portugal, by “expats,” privileged migrants who build community not with others who share an ethnic identity but rather with other international residents of similar class status, a phenomenon accelerated by the advent of remote work. By calling attention to the multicultural and pop aesthetics used in baby music classes at the Music Room, a private music school conducted primarily in English and marketed to expats, I show how expat children are sonically enculturated in cosmopolitan spheres and how expat cultural infrastructure plays a crucial role in promoting expat migration.